2022
DOI: 10.1111/aej.12680
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in patients with endodontic infections: A systematic scoping review of observational studies

Abstract: The aim of this study was to assess the prevalence and proportions of antimicrobial‐resistant species in patients with endodontic infections. A systematic scoping review of scientific evidence was accomplished involving different databases. Nine investigations were selected including 651 patients. Enterococcus faecalis was resistant to tetracycline (30%–70%), clindamycin (100%), erythromycin (10%–20%), ampicillin (9%) and azithromycin (60%). On the contrary, Prevotella spp., Fusobacterium spp., Peptostreptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Low susceptibility to erythromycin was also previously described in endodontic infections [ 42 ], and the augmentation of anaerobic resistance to clindamycin was also indicated in a recent systematic scoping review [ 42 ] with outcomes consistent with the great resistance of Prevotella spp. against penicillin [ 43 ].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Low susceptibility to erythromycin was also previously described in endodontic infections [ 42 ], and the augmentation of anaerobic resistance to clindamycin was also indicated in a recent systematic scoping review [ 42 ] with outcomes consistent with the great resistance of Prevotella spp. against penicillin [ 43 ].…”
Section: Discussionmentioning
confidence: 66%
“…against penicillin [ 43 ]. These findings are predominantly caused by the facility for beta-lactamase production among anaerobes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the heterogeneity of the randomized clinical trials examined in this systematic review precluded a more thorough study. Some recent systematic reviews [ 47 , 48 ] have revealed the exact same issues. The diverse behavior of systematic reviews, in terms of the clinical trials included, justifies the standardization of clinical techniques so that comparisons between clinical trials may be made without prejudice.…”
Section: Discussionmentioning
confidence: 87%
“…However, resistance to vancomycin was not observed in our collection. A systematic review by Ardilla et al [11], found no reports of vancomycin-resistant E. faecalis from root canals.…”
Section: Discussionmentioning
confidence: 99%